IDEOLOGY IN TRANSLATION OF CULTURAL LEXICAL ITEMS WITH REFERENCE TO PERBURUAN AND FUGITIVE - Christina Made Dwi Utami; Ida Ayu Made Puspani; Ni Wayan Sukarini (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThis study aimed at describing the translation strategies, methods, and ideologies in translationof an Indonesian novel Perburuan which was translated into English Fugitive. A Methodologyfor Translation proposed by Vinnay and Darbelnet (2004), was used to explain how thetranslation strategies applied at word or phrase level. Further, “V” Diagram proposed by NewMark (1988), was used to describe how the translation methods applied at sentence level. Attext level, translator’s orientations and extent of mediation proposed by Hatim and Munday(2004), and Munday (2006) were utilized to explain the implementation of The Ideology ofTranslating and The Translation of Ideology. It was found in the study that The Ideology ofForeignizing was more dominant to Ideology of Domesticating. It indicated that there wereattempts done by the translator to introduce the source language foreign cultural lexical itemsto the target language reader.Keywords: (In)visibility, cultural lexical items, the ideology of translating, the translation ofideologyABSTRAKPenelitian ini bertujuan untuk mendeskripsikan strategi, metode, dan ideologi penerjemahandalam terjemahan novel bahasa Indonesia Perburuan ke dalam novel bahasa Inggris Fugitive.Metodologi Penerjemahan yang diusulkan oleh Vinnay dan Darbelnet (2004) digunakan untukmenerangkan bagaimana strategi penerjemahan diterapkan pada level kata dan frasa.Selanjutnya, diagram “V” yang diusulkan oleh Newmark (1988) digunakan untukmendeskripsikan bagaimana metode penerjemahan diterapkan pada level kalimat. Pada levelteks, mediasi orientasi penerjemah dan perluasan mediasi yand diusulkan oleh Hatim danMunday (2004), dan Munday (2006) digunakan untuk menjelaskan Ideologi Penerjemahan danTerjemahan Ideologi. Dalam penelitian ini ditemukan bahwa Ideologi Foreignisasi lebihdominan daripada Ideologi Domestikasi. Hal ini mengindikasikan bahwa terdapat usaha yangdilakukan penerjemah untuk mengenalkan item-item leksikal budaya asing bahasa sumber kedalam pembaca bahasa target.Kata kunci: (In)visibility, item-item leksikal budaya, ideologi penerjemahan, terjemahanideologi